Serving the medical tourists in Malaysia: are local patients being put the second? / Norzayana Yusof and Herwina Rosnan. - Yusof, Norzayana; Rosnan, Herwina (Universiti Teknologi MARA Cawangan Selangor, 2020)
Despite the concern that local patients are being put the second, this article attempts to prove the otherwise. Ten in-depth interviews were conducted with a government division, medical doctors, and private hospitals serving medical tourists. Through Atlas.ti version 8, it is found that locals are still the primary focus as medical tourists only take about 10%, on average, of the total patients in these hospitals. Further, hospitals only went aggressive in medical tourism after their capacity expansion. This research suggests for the policy-makers to take the necessary actions in developing medical tourism industry while simultaneously catering for the locals’ needs.